Learning from Experience The Public Health Response to West Nile Virus, SARS, Monkeypox, and Hepatitis A Outbreaks in the United States - Stoto, Michael A. (RAND Corporation, 2005)
Describes the response of state and local health departments to outbreaks of Severe Acute Respiratory Syndrome (SARS), monkeypox, West Nile virus, and hepatitis A that took place from 1999 to 2003. In general, public health agencies demonstrated a robust ability to implement the major components of response to a public health emergency. Researchers found that the most pervasive problem involved communication difficulties within public health agencies and with public health partners.